Single-Frequency Time-Step Ionospheric Delay Gradient Estimation at Low-Latitude Stations - Jirapoom Budtho; Pornchai Supnithi; Susumu Saito (My University, 2020)
The irregularity of the local-area ionospheric delay is a primary impediment for Ground-Based Augmentation System (GBAS) services. Excessive ionospheric delay gradients may degrade aircraft positioning for high precision landing systems. Therefore, the spatial gradients of the nominal background ionosphere must be studied as their statistics will be sent to the approaching aircraft. For the well-known station-pair method, ionospheric delay gradient estimation requires at least 2 Global Navigation Satellite System (GNSS) reference stations. This method can be applied to both single or dual-frequency GNSS receivers. However, when the GNSS stations are far apart, it is not suitable for estimating the ionospheric delay gradients at short baselines, and the time-step method is an attractive alternative. In this work, we propose a single-frequency time-step method for ionospheric delay gradient estimation. Careful baseline length selection is needed, due to ionospheric piercing point movements. We applied our method to GNSS data in 2014, at the peak of the 24th solar cycle, and showed that the standard deviations of the vertical ionospheric delay gradients were comparable to those derived from the dual-frequency time-step method. The standard deviations of vertical ionospheric gradients, $\sigma _{\mathrm {VIG}}$ , ranged between 4 and 6 mm/km. The $\sigma _{\mathrm {VIG}}$ values around the equinoxes were ~1.5 mm/km greater than at other times.
Keywords: GNSS augmentation; Precise Point Positioning; GNSS positioning and interference